Peningkatan Keterampilan Menulis Tanggapan Terhadap Buku Fiksi Dan Nonfiksi Melalui Teknik Guiding Questions Pada Siswa Kelas VII A SMPN 1 Babadan - Anggie Bellia Putri; Panji Kuncoro Hadi; Sri Purwanti (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research was conducted based on the condition of students' writing skills, especially producing a text in class VII of SMPN 1 Babadan, which is low. The purpose of this study is to describe the improvement of response text writing skills in fiction and nonfiction books with the application of the Guiding Questions technique in class VIIA students of SMPN 1 Babadan in the 2022/2023 academic year. This Classroom Action Research uses a qualitative descriptive approach and uses data collection techniques, while the techniques used are tests and observations. To carry out the research, the researcher chose the research subject, namely class VIIA students of SMPN 1 Babadan with a student capacity of 25 children. From the results of data analysis obtained after conducting research using the Guiding Questions technique, it was able to improve the skills of writing responses to the fiction and nonfiction books they had read. It can be seen that the average student writing skills from the data obtained in cycle 1 is 75 and increased in cycle 2 which is 81. Directly proportional to the data also shows that students who meet and exceed the predetermined KKM have increased in each cycle, namely in cycle 1 60% and cycle 2 96%. Keywords: Response Writing Skills to Fiction and Nonfiction Books; Classroom Action Research (PTK); Guiding Questions.